O direito ao esquecimento em crimes de grande repercussão e a ressocialização criminal - Foletto, Juliana Oliveira (2023)
The monograph seeks to present an approach in relation to prisoners who committed crimes and who became of great repercussion in the media, starting to be constantly monitored by the press and their steps published in the news, some even having their lives presented in documentaries, making their crimes and their names are never forgotten by society, even after they have served their sentences. From this perspective we have the Federal Constitution that guarantees necessary individual rights; the Criminal Procedure that regulates due criminal process, from broad defense to conviction; the Criminal Execution Law that regulates the execution of sentences and the criminal rehabilitation of these individuals, providing the opportunity for them to return to live in society. On the other hand, there is a need for these individuals to achieve the right to be forgotten. Therefore, the proposal is to analyze and present the possibilities of a convict who has already paid his sentence being forgotten, when his case gained great repercussion. In the end, the study embraces the understanding that reliving and publishing the story of these prisoners after having served their sentences would be like convicting them again, bringing about the constant desire for revenge that a large part of society feels towards them. Bearing in mind that there is a predominance in the Superior Courts of supporting a greater right to the press, the solution to the problem would be to prioritize resocialization, with the creation of a bill that would add articles to the Criminal Execution Law to regulate the law, as The Legislature, given its typical function of legislating, is not linked to the decisions of the STF.